2018
DOI: 10.1093/nar/gky452
|View full text |Cite
|
Sign up to set email alerts
|

Triazole linking for preparation of a next-generation sequencing library from single-stranded DNA

Abstract: Next-generation sequencing of single-stranded DNA (ssDNA) is attracting increased attention from a wide variety of research fields. Accordingly, various methods are actively being tested for the efficient adaptor-tagging of ssDNA. We conceived a novel chemo-enzymatic method termed terminal deoxynucleotidyl transferase (TdT)-assisted, copper-catalyzed azide-alkyne cycloaddition (CuAAC)-mediated ssDNA ligation (TCS ligation). In this method, TdT is used to incorporate a single 3′-azide-modified dideoxyribonucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
(58 reference statements)
0
19
0
Order By: Relevance
“…The successful use of ‘click’ chemistry as a means of adapter addition was previously reported [41, 42]. Here, we executed ‘click’ reactions to generate oligo-modified nucleotides with oligonucleotide attached via the 5′ terminus prior to their incorporation into the growing DNA strand ( and S4, see Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful use of ‘click’ chemistry as a means of adapter addition was previously reported [41, 42]. Here, we executed ‘click’ reactions to generate oligo-modified nucleotides with oligonucleotide attached via the 5′ terminus prior to their incorporation into the growing DNA strand ( and S4, see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…The resulting extension products are amplified via PCR and subjected to standard Illumina paired-end sequencing. The forward sequencing read (R1) contains 16S rRNA V1-V2 regions starting from the specific priming site while the reverse read The successful use of 'click' chemistry as a means of adapter addition was previously reported [41,42]. Here, we executed 'click' reactions to generate oligo-modified nucleotides with oligonucleotide attached via the 5′ terminus prior to their incorporation into the growing DNA strand (Fig.…”
Section: Semi-targeted Sequencing Enables Capture Of a Priori Unknown Sequences Adjacent To The Target Sitementioning
confidence: 99%
“…A combinatorial approach for the discovery of splint-templated chemical ligations has been reported to identify DNA-compatible reactions to ligate terminally functionalised ONs [57]. Moreover, the generation of artificial backbone mimics has been shown for bridging 5 0 -S-phosphorothioester linkages (Ps) [58], PA [59][60][61][62], AM [61], urea [63], SQAM [63], TL1 [64] and TL3 [61]. Indeed, copper-catalysed azide-alkyne cycloaddition (CuAAC) to form TL3 was reported for the assembly of whole genes [12,65] and long RNA [9,10] from azide and alkyne modified shorter ONs.…”
Section: Nucleic Acid Formationmentioning
confidence: 99%
“…For example, the CuAAC click ligation of 3′-azido ONs with 5′-alkyne adaptor ONs to form TL 1 was recently described for the preparation of next-generation sequencing libraries. 17 However, the authors reported low replication efficiencies by several polymerases through TL 1 . Furthermore, click ligation has been used to assemble long DNA templates with isolated TL 6 modifications which can be replicated 9 , 29 or transcribed 8 , 9 by polymerases in bacterial 9 or mammalian 8 cells while retaining high fidelity read-through.…”
Section: Introductionmentioning
confidence: 99%